Multivalent methionine‐functionalized biocompatible block copolymers for targeted small interfering RNA delivery and subsequent reversal effect on adriamycin resistance in human breast cancer cell line MCF‐7/ADR - Wu, Yang; Zhang, Wei; Li, Tinghan; Ma, Rong; Chen, Dan; Zhang, Junying; Wu, Jianzhong; Tang, Jinhai (The journal of gene medicine, 2017)
Background Cationic polymers are outstanding representatives of the most efficient small interfering RNA (siRNA) vectors. Low cytotoxicity and siRNA protecting effect can be obtained with these cationic polymers via a variety of structural modifications. Nevertheless, the gap between their efficiency and the requirement for therapeutic processes is still noticeable. Methods A cationic polymer vector was synthesized via the copolymerization of N‐(1,3‐dihydroxy propan‐2‐yl)methacrylamide (DHPMA) and N‐(3‐aminopropyl)methacrylamide (APMA). Results APMA provides amine functionality that allows the conjugation of guanidine and methionine groups. Attributed to the hydroxy groups of DHPMA, the synthesized guanidine and methionine grafted DHPMA‐b‐APMA block copolymer (mDG) is water soluble and has good biocompatibility. The obtained mDG has high zeta potential, narrow molecular weight distribution, better membrane‐penetrating ability, high transfection efficiency, tumor cell targeting ability and high stability. Conclusions The synthesized polymer vector can deliver siRNA molecules into tumor cells and then reverse drug resistance by down regulation of P‐glycoprotein mRNA expression.